Surgical Treatment of Abdominal Aortic Aneurysms - Nuellari, Edmond; Kuci, Saimir; Kenga, Albana; Kosovrasti, Denis; Ibrahimi, Alfred (Gaceta Médica de Caracas, 2023)
ntroduction: Surgical treatment of abdominal aortic aneurysms poses a significant challenge in the field of vascular surgery, with numerous factors influencing operative technique and surgical outcome. Objective: This study aimed to assess the outcomes of open surgical treatment for patients with abdominal aortic aneurysms at the Vascular Surgery Service of Mother Teresa University Hospital Centre in Tirana, and provide recommendations for improving outcomes. Methods: A total of 206 patients who underwent transabdominal and retroperitoneal surgical access between January 2008 and December 2015 were included in the analysis.